Kajian Aspek Pemasaran dan Aspek Proyeksi Keuangan dalam Upaya Pengembangan Usaha Di Isola Resort Hotel – UPI Bandung - Wardhana, Wishnu (Politeknik Pariwisata NHI Bandung, 2017)
This study aims to assess the marketing aspect and the aspect of financial projections in Heritage Isola Resort Hotel as well as to analyze the influence of the dimensions of the product, place, price, and promotion of a business development plan to be undertaken and also evaluates the financial projections are measured using the method of Capital Budgeting with an evaluation tool discounted payback period net present value, internal rate of return, and profitability index in Isola Resort Hotel in Bandung. The method used in this research is survey method with descriptive explanations level by involving 46 respondents. Data collection techniques wing literature study, documentation studies, and field studies wing interviews and questionnaires. The data analysis technique used is qualitative analysis, quantitative analysis, and descriptive analysis. Qualitative analysis includes scores of respondents, and descriptive analysis. Results of research marketing activities in Isola Resort has generally shown good, with the results of the product dimension by 76.50%, 75.30% price dimension, a dimension of 80.20%, 71.50% of promotional dimension. As for the results of the evaluation based on the financial projections in Isola Resort Hotel is also in good condition. Projections of incomewas evaluated by using the method of capital budgeting by the calculation of the discowited payback period, net present value shows a positive result, the internal rate of return has the result is greater than the cost of interest rate of 12%, and the profitability index has a positive outcome, le more than 1. The findings of the study it can be concluded that the marketing aspect and the aspect of the financial projections is acceptable and to be implemented in Isola Resort business development efforts for the future.